Discrete-continuum coupling method to simulate highly dynamic multi-scale problems : simulation of laser-induced damage in silica glass /: simulation of laser-induced damage in silica glass. (2015) - Jebahi, Mohamed; Dau, Frederic; Charles, Jean-Luc; Iordanoff, Ivan
No abstract available